Impacts of Problem-Based Online Learning and Online Self-Efficacy on Students’ Ability in Writing Problem Solution Essays - Vitasmoro, Pamadya; Maftuhan, Muhamad; Jatmiko; Rahardini, Nimas Ayu; Dalu, Zaudah Cyly Arrum (JTP - Jurnal Teknologi Pendidikan, 2025)
This research aims to determine the impact of applying problem-based online learning strategy and online self-efficacy on the EFL students’ ability in writing a problem-solution essay. This research used quasi-experimental design. It was conducted at a reputable university in Kediri City of East Java, Indonesia, involving 81 first semester students of Pharmacy study program of Health Sciences Faculty. The students were divided into 2 groups: experimental group consisting of 41 students and control group consisting of 40 students. This research showed that the experimental group can improve their ability in writing a problem-solution essay better than the control group who did not gain online self-efficacy. Thus, having been taught how to apply a problem-based online strategy and applied online self-efficacy, students can improve their ability in writing a problem-solution essay.